To explore the reasons of the surge in sales of picture books during the COVID-19 Pandemic in China - Wangbei Tu; Kavitha Ganesan; Rose Patsy Tibok; Erlong Tang (Kriedt Enterprises Ltd, 2021)
During the COVID-19 pandemic, the shutting down of schools and offices, and he enforcement of home quarantine and other measures have led to an increase in digital online reading, which has boosted digital publishing. However, several studies have reported that more “screen exposure” time might lead to higher rates of abnormal psychological problems in preschool children's mood, conduct, attention, peer interaction and other aspects. In China, as a response to this perceived risk and reduce screen exposure among preschool children, families, society and the publishing industry have concentrated promoting printed picture books in these ways: parent-child reading of picture books in the family; storytelling, performance and other promotional activities in public and private libraries; and audible platforms promoted by the publishing industry and We-media.